2007
DOI: 10.1159/000101371
|View full text |Cite
|
Sign up to set email alerts
|

Coincident Activation of Th2 T Cells with Onset of the Disease and Differential Expression of GRO-Gamma in Peripheral Blood Leukocytes in Minimal Change Disease

Abstract: Background: Involvement of Th2 T cells/NFĸB in minimal change disease (MCD) has been postulated. A promising but unconfirmed glomerular permeability factor (GPF) from MCD T cells has been described. We explored whether GPF was the consequence of Th2 cell activation. Methods: Peripheral blood leukocytes (PBL) from 16 MCD patients and 7 normal controls were analyzed and the results were statistically compared. Results: Flow cytometry demonstrated a significant expansion of CD4+ T cell population and dramatically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…In contrast, studies examining IL-4 expression have been conflicting. Thus, although T cells have been reported to express high levels of IL-4 either spontaneously60 or after stimulation,61-63 other studies59,64,65 have not confirmed these findings.…”
Section: Alternative Views Of the Role Of Allergy In MCDmentioning
confidence: 89%
“…In contrast, studies examining IL-4 expression have been conflicting. Thus, although T cells have been reported to express high levels of IL-4 either spontaneously60 or after stimulation,61-63 other studies59,64,65 have not confirmed these findings.…”
Section: Alternative Views Of the Role Of Allergy In MCDmentioning
confidence: 89%
“…Regarding the MCD patients, our findings suggest an interesting role of Th2 cytokines in the outcome of disease, and particularly a strong association of increased urinary levels of Th2 cytokines at time of renal biopsy, with recurrent episodes of relapse during follow up. Association of MCD with allergic reactions is well-known, as is the shift to Th2 type immune response, especially in atopic children with MCD ( 32 , 33 ). IL-4 and IL-13 are increased during active phase of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Growth regulated protein (GRO)-γ is a potential candidate for the Th2-associated GPF in MCNS, as implicated in the function of endothelial cells. Furthermore, Adrogue et al (26) observed markedly higher levels of CD4 + T cells in patients with MCNS and hypothesized that the levels of IL-4, IL-8 and GRO were also higher in individuals with MCNS. An increase in the level of IL-8 was shown to change the permeability of the glomerular basement membrane (GBM) via reducing the synthesis of heparan sulfate proteoglycans (HSPGs) on the GBM, which eventually induced proteinuria in rats (27).…”
Section: Imbalance Of the Th1/th2 Response And The Role In Mcnsmentioning
confidence: 99%